Mothers’ perception of their involvement in expressive and creative therapy provided to their children at a special education school - Abramovski, Gal (Advances in Social Sciences Research Journal, 2020)
In light of the paucity of evidence on mothers’ involvement in expressive and creative therapy for adolescents with learning disabilities (LD) studying at special education schools, the current study examined mothers’ perceptions of their involvement in the therapy and of the relationship with the therapist. The sample comprised 18 mothers to adolescents with LD who were in therapy for at least one year. Data was collected via semi-structured interviews. The findings indicated several therapeutic issues as well as the special encounter that occurs between the therapeutic and educational domain. The discussion presents three main styles of maternal involvement. The theoretical implications of the results and their practical implications for expressive and creative therapy within schools are discussed.